Bloody genius [compact disc, unabridged] - Sandford, John, 1944 February 23- (Sandford, John, 1944 February 23- Virgil Flowers novels., 2019)
At the local state university, two feuding departments have faced off on the battleground of PC culture. When someone winds up dead, Virgil Flowers is brought in to investigate. He soon comes to realize he's dealing with people who, on this one particular issue, are functionally crazy. Among this group of wildly impassioned, diametrically opposed zealots lurks a killer, and it will be up to Virgil to sort the murderer from the mere maniacs.